2020
DOI: 10.1002/mrm.28331
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the accuracy and precision of TE‐dependent versus multi‐echo QSM using Laplacian‐based methods at 3 T

Abstract: Purpose Multi‐echo gradient‐recalled echo acquisitions for QSM enable optimizing the SNR for several tissue types through multi‐echo (TE) combination or investigating temporal variations in the susceptibility (potentially reflecting tissue microstructure) by calculating one QSM image at each TE (TE‐dependent QSM). In contrast with multi‐echo QSM, applying Laplacian‐based methods (LBMs) for phase unwrapping and background field removal to single TEs could introduce nonlinear temporal variations (independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 43 publications
1
59
0
Order By: Relevance
“…The magnetic susceptibility is estimated from the MRI signal phase, which is affected by the contributions from local microscopic tissue composition and macroscopic background fields which are removed via post-processing. QSM is also sensitive to acquisition parameters (particularly TE) (Biondetti et al, 2020) and tissue orientation with respect to the main magnetic field (Schweser et al, 2011; Wharton and Bowtell, 2012, 2015). Despite these limitations we found consistent differences in susceptibility values in the cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic susceptibility is estimated from the MRI signal phase, which is affected by the contributions from local microscopic tissue composition and macroscopic background fields which are removed via post-processing. QSM is also sensitive to acquisition parameters (particularly TE) (Biondetti et al, 2020) and tissue orientation with respect to the main magnetic field (Schweser et al, 2011; Wharton and Bowtell, 2012, 2015). Despite these limitations we found consistent differences in susceptibility values in the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…QSM is also sensitive to acquisition parameters (particularly TE) (Biondetti et al, 2020) and tissue orientation with respect to the main magnetic field (Schweser et al, 2011;Bowtell, 2012, 2015). Despite these limitations we found consistent differences in susceptibility values in the cortex.…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…Because of the known effects of moving spins on signal phase, it has been suggested that GRE images acquired for venous QSM require full first-order (i.e., velocity) flow compensation (Brown et al, 2014). Indeed, in the absence of flow compensation, vessels containing flowing blood can appear displaced on GRE magnitude (Deistung et al, 2009), GRE phase (Xu et al, 2014), SWI (Deistung et al, 2009), and QSM (Biondetti et al, 2020) images, potentially affecting the accuracy of both image-based vessel segmentation and venous susceptibility estimation inside segmented vessels. Fully flow-compensated sequences aim to suppress the additional phase induced by flowing spins (velocities in veins: 10-25 cm/s) at each echo time (TE) and along all three signal encoding directions of the Cartesian k-space trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…This would allow us to extend the analysis done by Karsa et al 73 on the effects of FOV and anisotropic voxels sizes, or the analysis by Biondetti et al on the effects of Laplacian-based single echo versus multiple-echo techniques. 74 Although the simulation framework is useful for optimizing protocols, the simulation in its current form is a static one. Consequently, flow artifacts (which build up when a large number of echoes are used), respiration-related B 0 fluctuations, 75 and spatial distortions associated with the readout bandwidth are not considered.…”
Section: Discussionmentioning
confidence: 99%